Human genetic variation and the genotype-phenotype problem 1 - Lyon, Gholson (Henry Stewart Talks, 2015)
Humans as mosaics, Biological indeterminacy & robustness, Parallel evolution, Genotype vs. phenotype, Categorical thinking misses complexity, Penetrance and expressivity, Nature and nurture, “Superpower” mutations, Identifying disease mutations, Genetics of neurodevelopmental disorders, Discovery of families with rare diseases and/or increased prevalence for syndromes, Genetic background and environmental perturbation influence phenotypic differences in severe mental illness